PENGARUH STRATEGIC LEADERSHIP TERHADAP COMPETITIVE POSITIONING MELALUI INTELLECTUAL CAPITAL TERHADAP PERUSAHAAN NON MANUFAKTUR - Clarence Daniel (Business Accounting Review, 2015)
Competition in the era of globalization of the international community was hit by devastating changes. This becomes very crucial because each company vying to dominate the market. Various ways done by companies that have good competitive positioning. The establishment of good competitive positioning cannot be separated from the leadership style that can create strategic vision and manage the company's operations are well that is strategic leadership. Strategic Leadership application of good leadership cannot be separated from the support of intellectual capital of the company.This study aims to examine the effect of the strategic leadership to competitive positioning through intellectual capital against non-manufacturing companies. The respondents were top-level management of various companies in Surabaya. The analysis technique used to process the data was Partial Least Square (PLS).The results showed that the strategic leadership affect the intellectual capital,  and the intellectual capital affect the competitive positioning where the intellectual capital was the intervening variable.